Структуризація інституціонального забезпечення рекреаційного природокористування в Україні - Коржунова, Н.В. (Економіка природокористування і охорони довкілля, 2013)
Проаналізовано сучасний стан інституціонального забезпечення рекреаційного природокористування. Визначено основні протиріччя раціонального використання рекреаційних ресурсів. Запропоновано напрями інституціоналізації рекреаційного природокористування. The current state of natural recreational resources is investigated. The main contradictions of recreational environmental management are defined. Discrepancy of institutional providing to new realities of economic transformations concerns to them first of all. Therefore, low efficiency of existing institutes of recreational environmental management demands their structurization. The analysis of the last publications shows that the perspective of institutional ensuring rational use of recreational resources isn't absolutely opened and demands further researches. The purpose of this work is development of the main directions of institutional ensuring recreational environmental management in Ukraine. First of all it is possible to distinguish from them: formation of the legal institutes directed on ensuring the rights of citizens on improvement and at the same time on rational use of natural recreational resources; improvement of economic institutes of recreational environmental management and introduction of system of strategic management at regional level. Further research is demanded by questions of a complex economic assessment of natural recreational resources and feature of a korporatization of economic space level.